Promoting Discovery Learning to Boost the Students’ English Writing in Vocational Schools - Aulia, Rahma; Prastikawati, Entika Fani; Ambarini, Ririn (research, training and philanthropy institution Natural Aceh, 2024)
This study aims to examine the impact of implementing the discovery learning (DL) approach on improving students' writing skills in English subjects. The study employed a quantitative method with a quasi-experimental design involving pre-tests and post-tests on two groups: a control group and an experimental group. The population of this study comprised 10th-grade students of Hospitality 1 and 2 at SMK N 6 Semarang in the 2024/2025 academic year, with Hospitality 1 as the control group and Hospitality 2 as the experimental group. In the experimental group, students were taught using the discovery learning (DL) approach, while the control group was taught without it. Data were collected through a writing test on recount texts and a closed questionnaire containing 15 questions to measure students' perceptions of the discovery learning approach. The data analysis, conducted using SPSS 27, revealed that the t-value (9.830) was greater than the t-table value (1.849) at a significance level of 0.025 with 27 degrees of freedom. This indicates that the alternative hypothesis (Ha) is accepted, and the null hypothesis (Ho) is rejected, showing a significant effect of discovery learning on students' writing skills. The questionnaire results demonstrated that students responded positively to this method, stating that discovery learning helped them become more active and engaged in the learning process. In conclusion, implementing the discovery learning (DL) approach significantly improves students' writing skills, making it an effective alternative for enhancing writing abilities in English language learning. The implication of this study suggests that teachers are encouraged to integrate discovery learning into their teaching strategies to foster active student participation and achieve optimal learning outcomes.